Діастолічна функція міокарда та особливості гемодинаміки малого кола кровообігу у хворих на гіпертонічну хворобу і їх медикаментозна корекція - Клименко, Вікторія Іванівна; Klimenko, V. I. (ДУ "Нац. наук. центр "Ін-т кардіології ім. акад. М. Д. Стражеска", 2002)
The dissertation is devoted to study the dependence of parameters of a pulmonary hemodynamics from an expressiveness of a diastolic dysfunction of a left ventricle with the consideration of the activity of sympaticoadrenal and renin-angiotensin-aldosteron systems, to reveal the hard degree of essentional hypertension and its effective medicines correction. Сomplex investigation of 137 patients and 30 healthy persons showed that the degree of hypertension is in direct dependence with arterial pressure and diastolic dysfunction of a left ventricle. Correlations between the basic parameters of diastolic and systolic functions of a left ventricle, systemic and pulmonary hemodynamics and pressure neure-humoral factors as well (adrenalin, noradrenalin in daily urine, rennin in blood's plasma) are evidenced the existence of common mechanism of development and becoming of changes in hemodynamics of the central and pulmonary blood circulations. It was proved the individual prescription of antihypertensive therapy by Enalaprili and Dylthyazemi with the consideration of the condition of diastolic function of a left ventricule and pulmonary hemodynamics.
Diastolic function of a myocardium and peculiarity of hemodynamics of the pulmonary blood circulation at the patients with essentional hypertension and its medicines correction
Keywords: гіпертонічна хвороба; діастолічна функція лівого шлуночка; легенева гемодинаміка; пресорні нейро-гуморальні фактори; антигіпертензивна терапія; гипертоническая болезнь; диастолическая функция левого желудочка; легочная гемодинамика; прессорные нейро-гуморальные факторы; антигипертензивная терапия; essentional hypertension; diastolic function of a left ventricle; pulmonary hemodynamics; pressure neure-humoral factors; antihypertensive therapy